Rehabilitation services for visually impaired children: early intervention or a long delay? - Rubo de Sousa Nobre Maria Inés; Temporini Edméa Rita; Newton Kara, José; Montilha Rita de Cássia letto (Human Occupation Journal, 2000)
The following aspects related to the care of visually impaired children were surveyed in a Low-Vision Stimulation Service in order to contribute to the improvement of the services it offers: age of the child at the first ophthalmologic consultation; person responsible for identifying the problem; knowledge of mothers concerning the vision problem of their child; and, age of the child at the beginning of stimulation. Twentyfive mothers of visually impaired children with ages varying from birth to 4 years were interviewed. In a general way, the problem had been identified before the children were 6 months old; however, only 50.0% of them had been attended to up to this age. In the great majority of the cases it was the mother who first perceived the vision problem of her child (48.0%), followed by other members of the family (28.0%) and, physicians (24.0%). Although the mothers disclosed some knowledge on the technical terminology concerning vision problems, they used it incorrectly. The Authors suggest that ophthalmologists should play a more active part in the early referral of visually impaired children to vision stimulation services.